COMPARACIÓN DE LA ACTIVIDAD MICROBIANA EN HOJARASCA ENTRE UN FRAGMENTO Y UN ÁREA CONTINUA DE BOSQUE NUBLADO DEL SECTOR OCCIDENTAL DE LA SABANA DE BOGOTÁ - Varela, Amanda; Laboratorio de Ecología de Poblaciones y Comunidades, Unidad de Ecología y Sistemática (UNESIS), Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2004)
Microclimatic changes are induced by the edge effect created in different habitat remnants due to fragmentation. These changes can affect important functional processes for terrestrial ecosystems, such as organic matter decomposition. A first approximation to effects on functional processes is to identify changes in the abundance and activity of decomposing microbiota. This study was performed in areas of cloud forest on the western side of the Sabana de Bogotá from May to August of 1998. A comparison was made between the microbial abundance and respiration and the litterfall moisture in a fragment and in a continuous forest area. Litterfall samples were taken at random at the edge and center of the fragment and in the center of the continuous forest area. The abundance of aerobic mesophylic fungi and bacteria was determined by dilution plate counts in the laboratory. Microbial  respiration activity was quantified as CO2 levels; percentage of litterfall moisture was determined gravimetrically. The bacterial abundance was higher in the fragment, particularly at its edge, while fungal abundance was higher only in the fragment with respect to the continuous forest. Microbial respiration was higher at the edge of the fragment. The litterfall moisture did not show differences. Litterfall moisture was poorly related to microbial abundance and respiration. The edge of the fragment had more impact on microbial abundance than on activity, because of other characteristics different from litterfall moisture. It is difficult to make predictions about the effects of these characteristics on litterfall decomposition rates and nutrient release. It is necessary to establish the magnitude of this effect on a temporal and spatial level, and if it occurs in other fragments of mountain cloud forest.